Respon Pertumbuhan dan Hasil Kale (Brassica oleracea L. Var. Acephala) Dalam Berbagai Media Tanaman Menggunakan Hidroponik NFT - Ukhtie Zakiyya; Bastaman Syah; Darso Sugiono (Universitas Respati Indonesia, 2026)
Kale plant (Brassica oleracea L. Var. Acephala) is a horticultural crop that belongs to the Brassicaceae family. Non-optimal cultivation practices and limited agricultural land are problems faced because agricultural land has been converted for community and residential development. Efforts are made with other alternatives, planting systems that save land, namely by using the NFT hydroponic system. The purpose of this study was to analyze and determine the best response to the use of planting media for the yield and growth of kale plants (Brassica oleracea L. Var. Acephala) in the NFT hydroponic system. This experiment used a single-factor RAL (Completely Randomized Design) environmental design experiment consisting of 6 treatments and 4 replicates, namely: A (Rockwool); B (Cocochip); C (Sponge); D (Floral Foam); E (Waste Tea Dip); F (Cotton). The data obtained were analyzed by F test analysis and Duncan Multiple Range Test (DMRT) further test at 5% level. The results showed a significant effect of various types of planting media on all parameters. Treatment C (Sponge) produced the greatest results in the parameters of plant height at 21 hst (14.54 cm), 28 hst (22.89 cm), 35 hst (26.96 cm), 42 hst (33.63); Number of leaves 21 hst (7.92 strands), 42 hst (15.88 strands); Leaf area (2480.44 cm²); Fresh weight yield per plant (205.96 g); Weight yield without roots per plant (156.29 g); and Root weight yield per plant (57.5 g).